Serum biomarkers of lipid, atherogenic index of plasma, electrocardiogram and fundus changes in hypertensive patients of central Nepal - Bastola, Pradeep; Singh, Jaya Prasad; Dhital, Bishnu Mani; Dahal, Polina (Journal of Chitwan Medical College, 2021)
Background: Hypertensive retinopathy, its ocular complication, is characterized by progressive metabolic disorders and structural damage to the retina. Lipids play an essential role in retinal hemostasis. The study was aimed to assess the prevalence of hypertensive retinopathy, the association between traditional lipid biomarkers and hypertensive retinopathy, and the predictive risk for future cardiac events using the atherogenic index of plasma in hypertensive patients of central Nepal. Methods: A hospital-based cross-sectional study was conducted in the Department of Ophthalmology, Chitwan Medical College, from 15 August 2021 to 30 October 2021. Ethical clearance was taken from the Institutional Review Committee (Ref: CMC-IRC/078/079-025). Convenience sampling was done to reach the sample size. Relevant data was entered in a proforma specified for the study. Data analysis was done using Statistical Package for the Social Sciences version 26, point estimate at 95% Confidence Interval (CI) was calculated along with frequency and proportion for binary data, p-value <0.05 was considered statistically significant. Results: The prevalence of hypertensive retinopathy was 34 (10.7%) (7.5-14.6 at 95% CI) in the study subjects. Gender wise females 167 (52.7%) outnumbered the males 150 (47.3%). Serum cholesterol level was the only biomarker significantly associated with the development of hypertensive retinopathy (p = 0.01). The mean atherogenic index of plasma in the study subjects was high (0.52). Conclusions: The prevalence of hypertensive retinopathy was lower in this study than similar studies done elsewhere. The atherogenic index of plasma was higher in the study subjects.